Clinical feasibility of a high-resolution thermal monitoring sheet for superficial hyperthermia in breast cancer patients - Bakker, Akke; Zweije, Remko; Kok, Henny Petra; Kolff, Merel Willemijn; Desiree van den Bongard, H. J.G.; Schmidt, Manfred; van Tienhoven, Geertjan; Crezee, Hans (Cancers, 2020)
Background: Accurate monitoring of skin surface temperatures is necessary to ensure treatment quality during superficial hyperthermia. A high-resolution thermal monitoring sheet (TMS) was developed to monitor the skin surface temperature distribution. The influence of the TMS on applicator performance was investigated, feasibility and ability to reliably monitor the temperature distribution were evaluated in a clinical study. Methods: Phantom experiments were performed to determine the influence of the TMS on power deposition patterns, applicator efficiency, and heat transfer of the water bolus for 434 and 915 MHz applicators. Clinical feasibility was evaluated in 10 women with locoregional recurrent breast cancer. Skin surface temperatures during consecutive treatments were monitored alternatingly with either standard Amsterdam UMC thermometry or TMS. Treatments were compared using (generalized) linear mixed models. Results: The TMS did not significantly affect power deposition patterns and applicator efficiency (1–2%), the reduced heat transfer of the water boluses (51–56%) could be compensated by adjusting the water bolus flow. Skin surface temperatures were monitored reliably, and no alteration of thermal toxicity was observed compared to standard Amsterdam UMC thermometry. Conclusion: Clinical application of the TMS is feasible. Power deposition patterns and applicator efficiency were not affected. Surface temperatures were monitored reliably.
CRIS-Team Scopus Importer:2020-12-18
Keywords: Hyperthermia; Quality assurance; Radiation oncology; Thermal monitoring